Impact of Ownership Structure and Companies’ Characteristics on Earnings Quality: An Empirical Study on Jordanian Industrial Joint Stock Companies - Al-Shahed, Rima (Jordan Journal of Business Administration, 2016)
This study aimed to produce evidence on the impact of ownership structure and companies’ characteristics on earnings quality. The study sample was based on 74 Jordanian companies, covering the period between 2005 and 2013. The results show that there is no evidence supporting the notion that ownership structure affects earnings quality. In contrast, the results reveal that companies’ characteristics (companies’ performance, growth and leverage) have a statistically significant negative effect on earnings quality.